Brazilian Exports : Climbing Down a Competitiveness Cliff - Canuto, Otaviano; Cavallari, Matheus; Guilherme Reis, José (World Bank, Washington, D.C., 2013)
This note examines in detail Brazil s export performance over the past 15 years, focusing not only on growth and composition, but also on different performance dimensions, including diversification, sophistication, and firm dynamics. The analysis uses international comparisons to better situate the Brazilian performance, and explores different databases, including firm-level data recently published by the World Bank. The note uses a recent diagnostic toolkit developed by the World Bank in order to suggest some hypotheses about the factors that have been inhibiting exports and industrial production expansion. Among the latter, it is noted how service sectors, as the largest beneficiaries from favorable terms of trade, accommodated larger wage increases and "exported" cost pressures to other sectors of the economy. Furthermore, although a stronger currency can be appointed as one of the elements behind the lower competitiveness in Brazilian exports, sluggish productivity performance and a real wage uptrend explain a significant part of the overall loss of competitiveness. This diagnostic reinforces the importance of resuming the agenda of microeconomic reforms, increasing the investment-to-gross domestic product ratio, and advancing toward better-skilled human capital.